Orthopedic manual therapy : an evidence based approach - Cook, Chad (Pearson Education, 2012)
This textbook has been extensively updated and presents all modern foundations of orthopedic manual therapy, including patient management, clinical reasoning, reflective practice, and problem solving. The comprehensive, regional approach to the body helps therapists synthesize new research, didactic knowledge, and clinical expertise.